FORMATION OF RESEARCH COMPETENCE IN FUTURE PRESCHOOL EDUCATION OF THE UNITED KINGDOM OF GREAT BRITAIN AND NORTHERN IRELAND - Ivanova, V.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Ukraine is heading to the European scientific community, so it is relevant to study the experience of the United Kingdom of Great Britain and Northern Ireland. Curriculum curricula of universities (Birmingham City, Middlesex, Nottingham, Swansea University) are analyzed and it is proved that one of the important features of British universities, which prepare specialists for preschool education, is to develop the research competence of the future students, professional tasks based on scientific knowledge. The purpose of the article is to analyze the curriculum curricula of the universities of the United Kingdom of Great Britain and Northern Ireland and to highlight the specificities of British universities where pre-service specialists are trained. Considering the role of curriculum content in the welfare of preschoolers, we note that the British National Preschool Education Program defines the requirements for the protection and well-being of preschoolers, and in the curricula of pre-baccalaureate baccalaureate studies, the students are taught modules that teach students children, legislation to support them, protection issues, the welfare of children, the impact of a supportive environment on children's learning; are aware of the role of early childhood professionals in the protection of children, their responsibilities for safety in care, upbringing and training. We believe that it is very important that students consider special educational needs and disabilities in modules, as future professionals of pre-school education will need this in the process of fulfilling their professional responsibilities in the workplace. However, it should be noted that not all universities meet the requirements of the national preschool education program for the protection of preschoolers. Based on the analysis of the content of the curriculum for the preparation of bachelors of pre-school education at the universities of the United Kingdom of Great Britain and Northern Ireland, we can conclude that the specific content of modules with a research orientation contributes to the formation of research competence, the solution of professional tasks, based on scientific knowledge and scientific knowledge, about teacher-teacher training that we consider to be one of the progressive ideas of pre-school teacher training that needs to be implemented in the process conducting educational reforms or the educational process of the Ukrainian higher education institution.